Management of wrist Ganglia by Aspiration Combined with Intralesional Steroid: A Prospective Study (Journal of Chittagong Medical College Teachers' Association, 2020)
Background: Ganglion is the most common be- nign soft tissue tumour of wrist and it represents about 60-70% of all such soft tissue tumours. There are various types of treatment options such as observation, aspiration, aspiration combined with intralesional steroids and surgical and arthroscopic excision. Many studies showed that surgical excision has the highest success rate but it has lots of dangers. So this study aimed that Aspiration with intralesional steroid, with its many advantages and success rate, may be the best choice for its treatment.  Materials and methods: We conducted the prospective study among 367 patients over a period of January 2017 to December 2018 in Surgery Outpatient Department, Chittagong Medical College Hospital, Bangladesh. After the procedure, patients were followed up every month for six months and then every 3 month for 1 year. Maximum follow up period was up to one year.Results: In our study it was found that there was female predominance with a male/female ratio of 1/1.41. Highest incidence was found in the age group between 21-30 years (37.1%).  68.4% patients presented with dorsal wrist ganglion and 31.6% with volar wrist ganglion. There was no steroid related local complication. Success rate of our study was 87.2% and recurrence rate was 12.8% within 6 months.Conclusion: Aspiration combined by intralesional steroid injection is an effective mode of management for wrist ganglion considering its success rate and post procedure complication rate.JCMCTA 2020 ; 31 (1) : 76-80